ON RELATIONS BETWEEN IRAN AND AZERBAIJAN - SAZHIN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2004)
To a great extent, stability and security in the Caucasus, in the Caspian Sea zone, and in Russia’s southern “soft underbelly” depend on the relations between Iran and Azerbaijan. The geostrategic importance of the Islamic Republic of Iran (IRI) and the Azerbaijanian Republic (AR) cannot be overestimated Indeed, Iran belongs to the Caucasian, Middle Eastern, and Central Asian regions; it is situated on the Caspian shores and has access to the Persian Gulf and the Gulf of Oman. In one way or another, the state is exposed to all the most painful problems of this vast region. None of the sores—ethnic, religious, military, or economic—or any of the problems related to refugees, drug trafficking, terrorism, and separatism can be successfully resolved without Tehran’s involvement. This is true even of the seemingly domestic problems plaguing individual parts of the region. It should be added that Iran has its ultimate value as a source of natural hydrocarbons and as an oil and gas transit territory. The country, with a population of 70 million, has one of the world’s largest armies (about 800,000). This is a decisive factor in West Asian regional politics, irrespective of either the domestic or foreign policy situation. In the Western Asian context, Azerbaijan is a key strategic factor because of its oil reserves and its bioresources. It is one of the region’s most developed industrial countries, which successfully masters high technologies; on top of this it is an important international transportation center. This explains why Iranian-Azerbaijanian relations have always been of great importance in international relations, and why the numerous complications in these relationships call for a detailed and pro-found analysis. Here I shall outline the most important of them.